1991
DOI: 10.1002/mrm.1910220104
|View full text |Cite
|
Sign up to set email alerts
|

Localized in vivo proton spectroscopy in the brain of patients with multiple sclerosis

Abstract: Localized proton spectroscopy was performed in 15 patients with acute or chronic multiple sclerosis (MS). Some of the patients were investigated serially, being given a total of 22 spectroscopic investigations. Resonances corresponding to free lipids were observed in six plaques. This was distinctly seen in two plaques at Days 70 and 85 after the occurrence of the plaques. A lesser content of lipids in plaques was observed as early as Day 10 and as late as nearly 1 year after occurrence. The relative concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(56 citation statements)
references
References 17 publications
4
51
0
1
Order By: Relevance
“…Because the truncation of k space and the position of VOI were similar in both normal volunteers and patients, one would expect the voxel bleed through to be similar in all patients and volunteers. However, the maximum observed SNR for 13,1524 lipids at the edge of the VOI in normal subjects and 17 of the MS patients was 6. In the 8 MS patients within the lipid-containing voxels, the maximum observed SNR was 21.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Because the truncation of k space and the position of VOI were similar in both normal volunteers and patients, one would expect the voxel bleed through to be similar in all patients and volunteers. However, the maximum observed SNR for 13,1524 lipids at the edge of the VOI in normal subjects and 17 of the MS patients was 6. In the 8 MS patients within the lipid-containing voxels, the maximum observed SNR was 21.…”
Section: Discussionmentioning
confidence: 75%
“…12,13,17 This interpretation is supported by the correlative studies of Ford and colleagues'* on experimental allergic encephalomyelitis (EAE).…”
mentioning
confidence: 79%
“…Multiple sclerosis-Multiple sclerosis is an autoimmune inflammatory demyelinating disease of the CNS which links axonal damage to reduced NAA levels in gray and white matter (Criste and Trapp, 2006). Clinical studies (Bruhn et al, 1992;Davie et al, 1994;Larsson et al, 1991;Leary et al, 1999) as well as a recent metanalysis of the use of MRS in multiple sclerosis (Caramanos et al, 2005) universally show decreased NAA levels associated with the progression of the disease. Reduced amounts of NAA and NAA/Cr in MRvisible lesions and in normal appearing white matter are readily documented Fu et al, 1998;Larsson et al, 1991;Tedeschi et al, 2002).…”
Section: Magnetic Resonance Spectroscopy and Imaging Of Naamentioning
confidence: 99%
“…However, pathological (Allen & McKeown, 1979) and quantitative MRSI studies (Armspach, Gounot, Rumbach, & Chambron, 1991;Filippi et al, 1995;Gasperini et al, 1996;Loevner et al, 1995) have shown that in patients with clinically definite MS, abnormalities also occur in the NAWM (Arnold et al, 1992;Davie et al, 1997;Davie et al, 1994;Fu et al, 1998;Husted et al, 1994;Narayana et al, 1998). Although the principal finding of MRS studies in patients with MS was a decrease in the NAA peak area, opposite results were obtained for other metabolites (Davie et al, 1994;Davies, Newcombe, Williams, McDonald, & Clark, 1995;De Stefano et al, 1995;Husted et al, 1994;Larsson et al, 1991). Despite the difficulties in interpreting data obtained in vivo, MRS provides direct information about metabolic variations and the damage to or integrity of myelin and axons, which are not revealed by traditional MRI (Arnold et al, 1994;Ferguson, Matyszak, Esiri, & Perry, 1997;Fernando et al, 2004).…”
Section: The Measurement Of N -A C E T L Y a S P A R T I C A C I D mentioning
confidence: 65%
“…Myelin and membrane constituents make a major contribution to the constituent of Cho; therefore, increased lesion cellularity and turn over may account for the observed increase in the level of Cho. However, an increase in Cho has been interpreted as an index of active or recent demyelination by some authors (Confort-Gouny et al, 1993;Davie et al, 1994;Kapeller et al, 2001;Larsson et al, 1991), an association suggested by the finding of an abundance of Cho-containing compounds in myelin and in all cell membranes, including those of inflammatory cells, in patients with MS (Brenner et al, 1993). This increase in the level of Cho may occur without significant clinical deterioration or disease activity.…”
Section: Wwwintechopencommentioning
confidence: 99%